MANAJEMEN KOMUNIKASI DINAS KOMUNIKASI DAN INFORMATIKA SUMATERA BARAT DALAM MENGATASI HOAX DI MEDIA SOSIAL - Defhany Defhany; Ria Edlina (Jurnal Ranah Komunikasi, 2022)
This research discusses the communication management carried out by the West Sumatra Komunikasi dan Informatika (Kominfo) Service in dealing with hoaxes on social media. The purpose of this research is to find out how communication management is carried out by the West Sumatra Kominfo Service in dealing with hoaxes on social media, especially during the Covid-19 pandemic. Panic and confusion of news regarding the news. One of the hoax news on social media regarding the Covid-19 pandemic is: The virus was spread due to a laboratory leak in Wuhan. The actions taken by the West Sumatra Communication and Informatics Service in Minimizing Hoax Information Always Continuing to Provide Information Using Various Media, Videotron, Providing Information About Awareness of the Dangers of Hoaxes and Controlling All Social Media and Websites Owned by the Institution, And Always Incessantly Carry Out Various Outreach, Seminars And Education To Communities In Several Regions About The Dangers Of Hoax And True Media Literacy. As well as holding educational talk shows about the dangers of hoax information on radio and TV stations which also collaborate with other government agencies so that the information conveyed is stronger and public confidence in the existence of hoax information is dangerous.